MODEL INTEGRASI PENCIPTAAN NILAI BERDASARKAN MODEL REFINED KANO DAN BLUE OCEAN STRATEGY - Sukwadi, Ronald; Yang, Ching Chow (Industrial and Systems Engineering Assessment Journal (INASEA), 2009)
It is not sufficient for a firm only to satisfy its customers. To be really successful, a firmÂ must create value for its customers and also derive value from its customers-that is a âwin-winâÂ strategy. In this study, the category of customer value will be redefined by suggesting a newÂ category of âcreative valueâ, then discusses how this category of âcreative valueâ relates to otherÂ forms of âvalueâ. Then, the concepts inherent in the refined Kano model and associated with theÂ Blue Ocean Strategy are explored. Using these concepts, an integrated model of âvalue creationâÂ are built and will be explained how this model can be used to determine appropriate improvementÂ actions to enhance customer value, and also enhance customer retention, customer acquisition,Â and customer margin, all of which make significant contributions to company profits. A case studyÂ is presented to illustrate the application of the model in practice.